Highly cited articles in malaria research: a bibliometric analysis. Issue 2 (3rd April 2017) - Kolle, Shankar Reddy; Vijayashree, M.S.; Shankarappa, T.H.
Abstract : Purpose: The purpose of this paper is to reveal the bibliometric characteristics of highly cited articles in Malaria research for the period of 1991-2015. Design/methodology/approach: The data of highly cited articles for the period of 1991 to 2015 were extracted from the Science Citation Index Expended of Web of Science. The keyword "Malaria" was used as topic term to search documents that contained this word in the title or keyword or abstract of the documents that published in 1991 to 2015. A total of 1, 614 articles having TC2015 = 100 were retrieved as highly cited articles for further analysis, and Microsoft excel was used for the analysis purpose. Findings: A total of 1, 614 of highly cited articles were published in the 230 journals for the period of 1991 to 2015, and majority of the articles were appeared in journals that have top impact factor. The articles published in the 2011s have greater average citations and authors per article. Six journals have produced almost a quarter of highly cited articles and remaining articles were published in 224 journals. Proceedings of the National Academy of Sciences of the USA was the most productive journal with 154 articles, which accounts for 9.53 per cent of the total articles, followed by Lancet (110; 6.81 per cent). We found degree collaboration value of 0.971 for the articles, which indicates the clear dominance of multiple authors in publication of highly cited articles in Malaria research. In this study, new indictor called P index was applied for the evaluation of the author's productivity. As per the p -value, the White, NJ has emerged as the most productive author with the p -value of 0.41 (61 articles), followed by Marsh, K ( p = 0.33), Nosten, F ( p = 0.32) and Snow, RW ( p = 0.31). The USA and the UK were the most productive countries. The article entitled as "Global and regional burden of disease and risk factors, 2001: systematic analysis of population health data" contributed by Lopez et al. (2006) was the most cited article with 2, 245 citations in 2015. Research limitations/implications: The data for the present study was limited to the publications that indexed in Science Citation index Expended of Web of Science. Originality/value: This paper would be useful to the researchers to know the trends and achievements in the Malaria research and also to the library and information science professionals in collection building process.